2009
DOI: 10.1073/pnas.0813306106
|View full text |Cite
|
Sign up to set email alerts
|

Role of COX-2 in epithelial–stromal cell interactions and progression of ductal carcinoma in situ of the breast

Abstract: Epithelial-stromal cell interactions have an important role in breast tumor progression, but the molecular mechanisms underlying these effects are just beginning to be understood. We previously described that fibroblasts promote, whereas normal myoepithelial cells inhibit, the progression of ductal carcinoma in situ (DCIS) to invasive breast carcinomas by using a xenograft model of human DCIS. Here, we report that the tumor growth and progression-promoting effects of fibroblasts are at least in part due to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(166 citation statements)
references
References 33 publications
8
156
0
2
Order By: Relevance
“…Loss of TGF-b type II receptor in fibroblasts cotransplanted with mammary carcinoma cells into mammary fat pad promoted tumor growth, invasion and metastasis (Cheng et al, 2005). In other studies using tumor xenograft models, CAFs were shown to accelerate the growth rate of tumors and enhanced tumor angiogenesis through mobilization and recruitment of endothelial cells (Hu et al, 2009;Orimo et al, 2005). Together, these results provide clear evidence on the active role of myofibroblasts on various steps of breast carcinogenesis.…”
Section: Role Of Cafs In Breast Cancer Development and Spreadsupporting
confidence: 53%
See 1 more Smart Citation
“…Loss of TGF-b type II receptor in fibroblasts cotransplanted with mammary carcinoma cells into mammary fat pad promoted tumor growth, invasion and metastasis (Cheng et al, 2005). In other studies using tumor xenograft models, CAFs were shown to accelerate the growth rate of tumors and enhanced tumor angiogenesis through mobilization and recruitment of endothelial cells (Hu et al, 2009;Orimo et al, 2005). Together, these results provide clear evidence on the active role of myofibroblasts on various steps of breast carcinogenesis.…”
Section: Role Of Cafs In Breast Cancer Development and Spreadsupporting
confidence: 53%
“…In addition, fibroblasts were shown to promote breast cancer cell invasion by upregulating MMP9 production (Wang et al, 2002). Recently, Hu et al, have shown that fibroblast MMP9 promotes breast cancer cells invasion in a coculture in vitro model (Hu et al, 2009). This indicates that MMP9 plays an important role in the cross-talk between breast tumors and their milieu.…”
Section: Mmpsmentioning
confidence: 96%
“…MCF10DCIS.COM-GFP (and shRNA derivatives) were obtained from K. Polyak (Harvard University, Cambridge, Massachusetts, USA), and 66cl4-luciferase cells (54) were obtained from H. Ford (University of Colorado, Boulder, Colorado, USA). Cells were cultured as described previously (1,31,55). Human dermal LECs (HDLECs) were obtained from PromoCell and maintained according to manufacturer's protocol with the following modifications: for routine culturing, plates were coated with 10 μg/ml Matrigel.…”
Section: Methodsmentioning
confidence: 99%
“…Arguably, aspirin may prove to be the prototype of low-cost, low-risk therapy that provides benefit via its effect on the microenvironment rather than the target epithelium. The prominent COX-2 involvement in progression of ductal carcinoma in situ has prompted the suggestion that its pharmaceutical inhibition could be beneficial (17,84).…”
Section: Implications For Cancer Preventionmentioning
confidence: 99%